Kun gzigs dbyangs char chen po Shel gyi me long : dang Nam mkhaʼi go laʼi tshul la dpyad pa bcas ; a detailed commentary on the Svarodaya (Yuddhavijaya) Tantra, the fundamental text for comprehending Tibetan astronomical, astrological, and calendrical theory - Mi-pham-rgya-mtsho, ʼJam-mgon ʼJu, 1846-1912 (Kham Kathok Tibetan Society, 1969)
Reproduction of manuscript arranged with four rectos to the page followed by the corresponding four vresos on the facing page.